PENGUJIAN UNSUR PENYALAHGUNAAN WEWENANG TERHADAP KEPUTUSAN DAN/ATAU TINDAKAN PEJABAT PEMERINTAHAN OLEH PTUN - Firna Novi Anggoro (Fiat Justisia: Jurnal Ilmu Hukum, 2016)
AbstractThe Act No. 30 year 2014 of governance administration give the atribution authority to receive, examine and decide abuse of authority whether there were any abuse of authority in decision and/or the act of government officials. Providing authority by PTUN to examine abuse of authority as a result of the absence of forum a defense for agencies and/or government officials in thought have done abuse in addition to criminal law. Agencies and/or government officials feel victims of criminal acts the policies the government was taken. Problems research this is how to examine abuse of authority of the decision and/or the act of government officials by PTUN and the implications law decisions PTUN for an applicant who expressed is or no abuse of authority on the criminal justice process. Methods used in this research is with the statute approach and case approach. The data used was primary and secondary data. Data analysis be done in legal analysis.The results of the study showed that construction examine to abuse of authority of the decision and/or the act of government officials by PTUN covering authority PTUN which is based on the act No. 30 year 2014 and PERMA No. 4 year 2015. Substance to examine pertaining to a subject entreaty namely agencies and government officials and object entreaty the decision and/or the act of government officials. Given the procedure examine limits namely after the introduction of the results and supervision APIP before the presence of criminal justice process. Legal implications of the administrative court decisions stating that decision and/or the act of government officials there are abuse of authority can continue in criminal justice process. Along proven there are malicious intent (mens rea). Next, implication law decisions PTUN who stated that the decision and/or the act of government officials no abuse of authority, basically not to continue to the criminal justice process, because they did not fulfill bestanddelict from act the crime of corruption. Keywords: Abuse of Authority, Decision and/or the Act of Government Officials, Administrative Court AbstrakUndang-Undang No. 30 Tahun 2014 tentang Administrasi Pemerintahan memberikan atribusi kewenangan kepada PTUN untuk menerima, memeriksa, dan memutus ada atau tidaknya unsur penyalahgunaan wewenang dalam keputusan dan/atau tindakan Pejabat Pemerintahan. Pemberian kewenangan oleh PTUN dalam menguji unsur penyalahgunaan wewenang muncul sebagai akibat dari tidak adanya forum pembelaan bagi Pejabat Pemerintahan yang diduga telah melakukan penyalahgunaan wewenang selain di ranah hukum pidana. Pejabat Pemerintahan seringkali menjadi korban kriminalisasi terhadap kebijakan yang diambil. Permasalahan penelitian ini adalah bagaimana konstruksi pengujian unsur penyalahgunaan wewenang terhadap keputusan dan/atau tindakan Pejabat Pemerintahan oleh PTUN dan implikasi hukum putusan PTUN bagi pemohon yang dinyatakan ada atau tidak ada unsur penyalahgunaan wewenang terhadap proses pidana. Metode yang digunakan dalam penelitian ini adalah dengan pendekatan undang-undang (statute approach) dan pendekatan kasus (case approach). Data yang digunakan adalah data primer dan data sekunder. Analisis data dilakukan secara analisis hukum (legal analysis). Hasil penelitian menunjukan bahwa konstruksi pengujian unsur penyalahgunaan wewenang terhadap Keputusan dan/atau tindakan Pejabat Pemerintahan oleh PTUN meliputi wewenang PTUN yang didasari atas Undang-Undang No. 30 Tahun 2014 dan PERMA No. 4 Tahun 2015. Substansi pengujian berkaitan dengan subjek permohonan yaitu Badan atau Pejabat Pemerintahan serta objek permohonan yaitu Keputusan dan/atau tindakan Pejabat Pemerintahan. Prosedur pengujian diberikan batasan yaitu setelah adanya hasil pengawasan APIP dan sebelum adanya proses pidana. Implikasi hukum Putusan PTUN yang menyatakan bahwa keputusan dan/atau tindakan Pejabat Pemerintahan ada unsur penyalahgunaan wewenang dapat berlanjut pada proses pidana (criminal process) sepanjang terbukti ada niat jahat (mens rea). Selanjutnya, implikasi hukum Putusan PTUN yang menyatakan bahwa keputusan dan/atau tindakan Pejabat Pemerintahan tidak ada unsur penyalahgunaan wewenang, pada dasarnya tidak dapat dilanjutkan pada proses pidana, karena tidak terpenuhinya bestand delict (delik inti) dari Pasal 3 UU Tipikor. Kata Kunci: Penyalahgunaan Wewenang, Keputusan dan/atau Tindakan Pejabat Pemerintahan, PTUN